Gesù Cristo il Filosofo - Relja, Hrvoje (Alpha omega, 2013)
This article demonstrates the novelty of the worldview introduced by Jesus Christ. First of all, by showing the deficiency of all the worldviews that preceded his appearance and by pointing out the conflict between logos – philosophy and mythos – religion as their main characteristic. Then, by explaining how the Church, in virtue of presenting Jesus Christ to those currents of thought, chose the path of philosophy, thus indicating the rationality of the Revelation fulfilled in Jesus Christ. Finally, by showing that the Church finds the arguments for such a position in Revelation itself, which contains common sense arguments that Jesus Christ is the manifestation of the Logos itself and that the philosophy of Jesus Christ, although revealed, is the true philosophy, one that satisfies human reason and the aspirations of the human heart.